Legal Position of Lex Specialis Derogat Legi Generali in the Implementation of Special Autonomy for Papua - Maria Yeti Andrias; Yulianus P Aituru (Faculty of Law, Universitas Pekalongan, 2021)
This magazine discusses the Legal Position of Lex Specialis Derogat Legi Generali within the Implementation of Special Autonomy within the Regions, with a focus on case research in Papua. This abstract presents a summary of the contents of the Journal, which includes history troubles, hassle system, goals, studies methods, effects of analysis, and conclusions.Background This journal illustrates the importance of special autonomy as a form of unique answer for regions with unique traits and troubles. The components of the hassle includes questions about the meaning of unique autonomy, the records of the implementation of special autonomy in Papua, in addition to the feature and scope of this unique autonomy.The reason of this magazine is to analyze the criminal role of Lex Specialis Derogat Legi Generali in the implementation of special autonomy, and to understand the function of unique and trendy laws and rules inside the context of unique autonomy.The studies technique used is literature observe by using amassing facts from diverse reliable assets together with laws, selections of the Constitutional Court, and related scientific journals.The effects of the evaluation screen that the principle of Lex Specialis Derogat Legi Generali is the important thing in resolving felony conflicts between special autonomy policies and national popular regulations. The application of Lex Specialis offers priority to important policies that observe in the region, as a result imparting extra authority according to the distinctiveness and desires of the place.Conclusion this journal emphasizes the significance of increasing felony attention in society to assist the implementation of unique autonomy. Improving the prison device and strengthening the judiciary are also important in order that unique autonomy can run well and provide most desirable benefits for the area people. Community collaboration and involvement also are critical elements within the achievement of unique autonomy, in order that the network feels they have an energetic role in development and choice-making in their region